iCEBc: A new predictor for hemodialysis need in patients with crush injury—experience from the february 6, 2023, Turkey earthquake - Bülent Güngörer; Bekir Demirtaş; Harun Kundi; İzzet Özgürlük; Metin Ocak (Hong Kong Journal of Emergency Medicine)
Abstract Objective Early diagnosis and treatment of acute renal failure is critical for reducing mortality and morbidity in patients with crush syndrome (CS), which necessitates hemodialysis (HD) treatment in 75% of CS cases. This study aimed to evaluate whether the index of cardio electrophysiological balance‐corrected (iCEBc) and/or other electrocardiographic parameters could predict the need for HD among patients who had suffered from CS following the February 6, 2023 earthquakes in Kahramanmaraş, Turkey. Methods This single‐center retrospective case‐control study included 130 patients diagnosed with CS. They were divided into two groups: the HD group (n = 56) and the non‐HD group (n = 74). Results The study group had a mean age of 40.6 ± 16.1 years and 71 (54.6%) were males. iCEBc values in the HD group were significantly higher than those in the non‐HD group (p < 0.001). Multivariate regression revealed that high iCEBc (p = 0.029, odds ratio: 2.286, and 95% confidence intervals: 1.086–4.811), creatine kinase (p < 0.001, OR: 1.037, and 95% CI: 1.016–1.058), and white blood cell count (p = 0.002, OR: 1.112, and 95% CI: 1.038–1.191) were independent predictors of HD treatment. iCEBc > 4.67 predicted the need for HD with 75.0% sensitivity and 56.8% specificity. A new scoring system, ranging from a minimum of 0 to a maximum of 10 points, has been designed. In patients with a score of ≥5, the need for dialysis was approximately seven times higher (p < 0.001, OR: 6.623, and 95% CI: 3.002–14.612). The area under the curve (AUC) of the new scoring system for predicting dialysis necessity was 0.803 (95% CI: 0.729–0.876 and p < 0.001). Conclusion iCEBc and new scoring system are a simple, rapid, repeatable, and inexpensive parameter that can effectively predict the need for HD treatment in patients with CS.